The Medicolegal Evaluation of Womens Sexual Dysfunctions - Safran, Nurhas; Alkan, Nevzat (The Bulletin of Legal Medicine, 2000)
Sexual dysfunctions are very frequent among man and woman. It has a very important role in maintaining a good family relationship. If this relationship breaks down, the couples may go to court to divorce, as they think their family relationship will not continue. Forensic medical specialists are accepted as an expert, for several occasions as well as assessment of sexual dysfunctions, at the courts. However our observations reveal that problems of sexual dysfunction regarding men are frequently required to be assessed more by courts. Sexual dysfunctions of women are complex as men's, and on the contrary of general beliefs women's sexual dysfunctions are more common than men. In our country, there are only a few studies because lifestyle of Turkish family is rather obscene about sexuality. The purpose of this study is, to present general information about sexual dysfunctions among women and to examine both forensic and legal aspects of this topic. There seems to be a need for increase in tile number of the researchers for this topic.Keywords: Sexual dysfunction, woman, forensic medicine, divorce.
Keywords: sexual dysfunction; woman; forensic medicine; divorce